Acute non puerperal inversion of uterus with large submucous fibroid - Singh, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Non-puerperal uterine inversion (NPUI) is rare and is usually precipitated by tumors sited at the fundus of the uterus which exert traction force to cause the inversion Acute inversion is more dramatic and characterized by severe pain and bleeding and patient might go into shock whereas chronic is insidious with irregular bleeding and vaginal discharge. In this paper, we present a case of a 55years old woman who presented with retention of urine and menorrhagia for 3 months followed by acute NPUI secondary to a submucous fundal fibroid due to which patient went into sudden shock. Finally laparotomy had to be done followed by total abdominal hysterectomy and bilateral salpingo-oophorectomy.